COMPARATIVE EFFICACY OF PROGESTERONE ASSAY AND ULTRASONOGRAPHY FOR EARLY PREGNANCY DIAGNOSIS IN BUFFALOES - NAKHASHl, H C; NAKHASHl, H C; SUTHAR, B N; SHARMA, V K; SIDDIQUEE, G M; PATEL, J B; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
The comparative efficacy of ultrasound scanning and plasma P 4 assay was studied to diagnose early pregnancy in Mehsana buffaloes. The sensitivity and specificity for early pregnancy diagnosis through ultrasound scanning on days 20, 25 and 30 of gestation were 75.0,66.7 and 1_00; 66.7, 100 and 100, respectively. Both negative and positive predicUve values improved as the pregnancy advanced whereas, diagnostic accuracy was 100 per cent using ultrasonography against 86.2 per cent by P4 assay on 301h day post breeding. It was possible to visualize the embryonic vesicle and/or embryo clearly in every animal that was found pregnant from day 30 onwards from breeding. The technique of ultrasound scanning facilitated the diagnosis of all pregnant animals as early as on day 25 postservic.